The importance of probiotics and prebiotics in nutritional health during adulthood (Research, Society and Development, 2022)
The Probiotics are part of the so-called functional foods, whose main target is the intestinal mucosa. Different probiotics are capable of inducing pro-inflammatory, anti-inflammatory or secretory responses that can inhibit carcinogenesis. Therefore, this study aimed to: Understand about the importance of probiotics and prebiotics in adulthood. And as specific objectives: conceptualize about probiotics and prebiotics; indicate the effectiveness of these microorganisms for health and the fight against pathologies in adulthood; understand about the importance of functional foods that contain probiotics and prebiotics in the treatment of chronic pathologies; show how probiotics and prebiotics are beneficial in improving gastrointestinal functioning. The methodology applied to this research was bibliographic of a qualitative nature, with a systematic review as the basis for its elaboration. Data for analysis were collected from scientific articles, books and magazines, accessed from bibliographic sources on platforms such as Google Scholar, and Scielo. The inclusion criteria adopted in this study were based on the proposed theme, emphasizing the free access articles in Portuguese and a foreign language already published, related to the descriptors revised according to the VHL - Virtual Health Library, DeCS - Descriptors in Sciences Health, being: Probiotics; Prebiotics; Health. Therefore, this research contributes to the scientific knowledge applied to probiotics and prebiotics, and to Nutrition professionals with regard to the handling of these foods in the diet of the population.